Observed and simulated depletion layers with southward IMF - N. C. Maynard; W. J. Burke; J. D. Scudder; D. M. Ober; G. L. Siscoe; W. W. White; K. D. Siebert; D. R. Weimer; G. M. Erickson; J. Schoendorf; M. A. Heinemann (Annales Geophysicae, 2004)
We present observations from the Polar satellite that confirm the existence of two types of depletion layers predicted under southward interplanetary magnetic field (IMF) conditions in magnetohydrodynamic simulations. The first depletion type occurs along the stagnation line when IMF BX and/or dipole tilt are/is present. Magnetic merging occurred away from the equator (Maynard et al., 2003) and flux pile-ups developed while the field lines drape to the high-latitude merging sites. This high-shear type of depletion is consistent with the depletion layer model suggested by Zwan and Wolf (1976) for low-shear northward IMF conditions. Expected sites for depletion layers are associated with places where IMF tubes of force first impinge upon the magnetopause. The second depletion type develops poleward of the cusp. Under strongly driven conditions, magnetic fields from Region 1 current closure over the lobes (Siscoe et al., 2002c) cause the high-latitude magnetopause to bulge outward, creating a shoulder above the cusp. These shoulders present the initial obstacle with which the IMF interacts. Flow is impeded, causing local flux pile-ups and low-shear depletion layers to form poleward of the cusps. Merging at the high-shear dayside magnetopause is consequently delayed. In both low- and high-shear cases, we show that the depletion layer structure is part of a slow mode wave standing in front of the magnetopause. As suggested by Southwood and Kivelson (1995), the depletions are rarefactions on the magnetopause side of slow-mode density compressions. While highly sheared magnetic fields are often used as proxies for ongoing local magnetic merging, depletion layers are prohibited at merging locations. Therefore, the existence of a depletion layer is evidence that the location of merging must be remote relative to the observation.